Analysis of Blood Flow Through an Overlapping Mild Stenosis - Rana, Tuk Bahadur; Gautam, Puspa Nidhi; Kafle, Jeevan (Nepal Journal of Mathematical Sciences, 2025)
The abnormal narrowing of the arteries due to stenosis significantly impacts cardiovascular function by restricting the blood flow. The progression of stenosis, influenced by factors such as blood viscosity, shear stress, and artery curvature, can lead to severe complications, including strokes and heart failure. In this article, we have focused on overlapping stenosis, which poses a unique challenge due to its irregular shapes and greater obstruction of blood flow. This study analytically investigates key hemodynamic parameters such as velocity, volume flow rate, pressure drop, pressure drop ratio, shear stress, and shear stress ratio as blood passes through the overlapping region, treating blood as a Newtonian fluid. The velocity and volume flow rate decrease heavily due to overlapping stenosis, and the pressure drop and shear stress increase in the overlapping stenotic region. With the help of this change, we can predict the real situation of cardiovascular disease, and many lives can be saved using this information.